Espaços livres de uso público em Ouro Preto (MG): heranças históricas, desafios contemporâneos - Alice Viana de Araujo (2018)
This research aims to understand the reasons why the public open spaces of the Historic Center of Ouro Preto, although being so alive during some festive events, appear to be so uninviting in daily life. In day-to-day life, the numerous squares and other open spaces of the old center end up being more used as spaces of passage and parking of vehicles, than as equipments dedicated to leisure activities, both of passive (contemplation, rest, socialization, personal entertainment) and active nature (sports and recreation). The lack of opportunities to stay in these places affects not only the local population but also the tourists, and much of the leisure and exchange experiences end up taking place in closed, and often private, environments. Thus, we made a brief inventory of all public open spaces contained in the historic center, researching its history, its problems and potentialities, as well as their articulation in a system of public open spaces. We also searched all the physical, social and legal restraints that could impact the appropriations in these spaces and also sought to identify the real challenges for their adaptation to the various demands of contemporary society, surpassing its historical-patrimonial value and reaching a new meaning.